2021
DOI: 10.1002/ecy.3549
|View full text |Cite
|
Sign up to set email alerts
|

Arboreality drives heat tolerance while elevation drives cold tolerance in tropical rainforest ants

Abstract: Determining how species thermal limits correlate with climate is important for understanding biogeographic patterns and assessing vulnerability to climate change. Such analyses need to consider thermal gradients at multiple spatial scales. Here we relate thermal traits of rainforest ants to microclimate conditions from ground to canopy (microgeographic scale) along an elevation gradient (mesogeographic scale) and calculate warming tolerance to assess climate change vulnerability in the Australian Wet Tropics B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
26
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 49 publications
4
26
1
Order By: Relevance
“…Our analyses highlight that habitats impose local variability in maximum peak temperature and heat tolerance, not influencing minimum temperature or cold tolerance. This similar contrasting pattern appears in other terrestrial ectotherms (Frishkoff et al 2015, Kaspari et al 2015, Nowakowski et al 2017, Pintanel et al 2019, Anderson et al 2022, Leahy et al 2022. The divergence on the variation of extreme environmental temperatures (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…Our analyses highlight that habitats impose local variability in maximum peak temperature and heat tolerance, not influencing minimum temperature or cold tolerance. This similar contrasting pattern appears in other terrestrial ectotherms (Frishkoff et al 2015, Kaspari et al 2015, Nowakowski et al 2017, Pintanel et al 2019, Anderson et al 2022, Leahy et al 2022. The divergence on the variation of extreme environmental temperatures (i.e.…”
Section: Discussionsupporting
confidence: 69%
“…Distributional records are the focus of the Global Ant Biodiversity Informatics (GABI) Project (Guenard et al, 2017). Genomes are being collated through Fourmidable (Wurm et al, 2009) (Diamond et al, 2012;Leahy et al, 2021;Penick et al, 2017;Roeder et al, 2021); dietary traits, such as nitrogen stable isotope composition, have been used extensively in recent studies that explore the position of ants on a spectrum from herbivores to predators (Davidson, 2005;Davidson et al, 2003;Gibb & Cunningham, 2013); and key life-history traits such as colony size, have featured in studies that cover a broad range of species (e.g. Burchill & Moreau, 2016;Kaspari & Vargo, 1995).…”
Section: Current Data Strengths and Opportunitiesmentioning
confidence: 99%
“…This is especially so in hotter microenvironments such as forest canopy in ants (Leahy et al. 2022) or in open sunlit temporary ponds in aquatic subtropical amphibian tadpoles (Duarte et al. 2012; Sanabria et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, their warming tolerance is low, in agreement with current evidence showing that upper tolerances in ectotherms from low latitudes are close to the current maximal experienced temperatures. This is especially so in hotter microenvironments such as forest canopy in ants (Leahy et al 2022) or in open sunlit temporary ponds in aquatic subtropical amphibian tadpoles (Duarte et al 2012;Sanabria et al 2021). Recently, Campos et al (2021) have reported decreased warming tolerances for low-latitude South American freshwater fishes that would be at high risk of suffering heat impacts.…”
Section: Discussionmentioning
confidence: 99%